Provision of smoking cessation support in UK primary care: impact of the 2012 QOF revision - Szatkowski, Lisa; Aveyard, Paul (Royal College of General Practitioners, 2016)
Background Before 2012, UK GPs were paid only to offer cessation advice to smokers and only to those with smoking-related disease, a minority of all smokers. From 2012, GPs are now paid to offer all smokers referral for behavioural support and medication to assist cessation at least once every 2 years.